An alkalinized V2CT x MXene materials, methods of making and using the same

CN122897410APending Publication Date: 2026-10-13ANHUI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611011128.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-08
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

其中,电化学传感器使用寿命较短、易受环境干扰;半导体金属氧化物传感器多需高温工作,能耗高且选择性较差

Benefits of technology

[0025]优选的,焙烧的温度为650~750℃,焙烧的时间为20~40min。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122897410A_ABST
    Figure CN122897410A_ABST
Patent Text Reader

Abstract

This invention provides an alkaline V2CT x MXene materials, their preparation methods, and applications include the following steps: grinding V2AlC with a composite salt to form a tablet; grinding the composite salt and Lewis acid salt to obtain a eutectic salt; coating the eutectic salt onto the tablet and then calcining, washing, drying, and grinding to obtain V2CT. x MXene material; V2CT x MXene material was reacted in sodium hydroxide solution to produce alkalized V2CT. x MXene material. This invention utilizes V2CT... x Alkali treatment of MXene materials promotes the interlacing and recombination of nanosheets, forming an open, three-dimensional hierarchical structure. This solves the problem of easy stacking of nanosheets and increases the alkali-induced V2CT. x The gas diffusion channels in MXene materials facilitate the exposure of more surface active sites, enabling the alkalization of V2CT. x MXene materials exhibit high selectivity for ammonia at room temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of ammonia sensor technology, specifically to an alkalized V2CT. x MXene materials, their preparation methods, and applications. Background Technology

[0002] Ammonia is an alkaline, toxic gas with a pungent odor, widely present in various fields such as chemical production, livestock farming, and wastewater treatment. Long-term exposure to low concentrations of ammonia can damage the human respiratory system and eyes, while high concentrations can cause poisoning and even death. Furthermore, ammonia leaks frequently lead to poisoning and explosions, posing a potential threat to safe production. Therefore, achieving rapid, highly selective, and sensitive detection of ammonia at room temperature is of significant practical importance and application value for ensuring both industrial safety and personal health.

[0003] Currently, common ammonia sensors mainly include electrochemical sensors, semiconductor metal oxide sensors, and optical sensors. Among them, electrochemical sensors have a relatively short lifespan and are easily affected by environmental interference; semiconductor metal oxide sensors often require high temperatures to operate, have high energy consumption, and poor selectivity. Summary of the Invention

[0004] The technical problem to be solved by this invention is how to provide an alkalized V2CT that exhibits high selectivity for ammonia at room temperature. x MXene material.

[0005] The present invention solves the above-mentioned technical problems through the following technical means:

[0006] The first aspect of the present invention provides an alkaline V2CT x The preparation method of MXene material includes the following steps: S1. V2AlC is ground with a composite salt and then compressed into tablets; the composite salt and Lewis acid salt are ground to obtain a eutectic salt; the eutectic salt is coated on the tablets and then calcined, washed, dried, and ground to obtain V2CT. x MXene material; Lewis acid salts include one or more of copper chloride, cobalt chloride, nickel chloride, or silver chloride; S2, V2CT x MXene material was reacted in sodium hydroxide solution, and after the reaction, it was washed, dried and ground to obtain alkalized V2CT. x MXene material.

[0007] Beneficial effects: This invention prepares V2CT without inert functional group F by molten salt method. x MXene material is beneficial for V2CT x The response of MXene materials to ammonia gas; V2CT prepared in this invention xMXene materials possess a layered structure and adjustable interlayer spacing. Their surface is rich in -OH and -O functional groups, providing more coordination sites and hydrogen bonding sites, enabling them to interact with ammonia molecules. Further alkalization treatment leads to a three-dimensional hierarchical structure, solving the problem of easy nanosheet stacking and increasing the alkalization V2CT. x The gas diffusion channels of MXene materials facilitate the exposure of more accessible surface active sites, promoting the adsorption and transport of ammonia molecules, and enabling the alkalization of V2CT. x MXene materials exhibit rapid response and high selectivity to ammonia at room temperature.

[0008] Preferably, the composite salt is a mixture of NaCl and KCl in a molar ratio of 1:1.

[0009] Preferably, the mass ratio of V2AlC to the composite salt is 1:5.

[0010] Preferably, the molar ratio of V2AlC to Lewis acid salt is 1:4.

[0011] Preferably, the molar ratio of the composite salt to the Lewis acid salt is 2:0.1.

[0012] Preferably, the roasting temperature is 650~750℃ and the roasting time is 20~40min.

[0013] Preferably, the heating rate during roasting is 5~10℃ / min.

[0014] More preferably, in S1, the washing process involves washing with water multiple times, then washing with APS solution for 1 hour, and then washing with water multiple times again.

[0015] Preferably, the concentration of the sodium hydroxide solution is 1~5M.

[0016] Preferably, the reaction time is 10-12 hours.

[0017] More preferably, the drying temperature is 60~80℃ and the drying time is 12~24h.

[0018] The second aspect of the present invention provides the above-mentioned alkaline V2CT x Preparation method of MXene material to prepare alkaline V2CT x MXene material.

[0019] A third aspect of the present invention provides a V2CT x The preparation method of MXene material involves grinding V2AlC with a composite salt to form a tablet; grinding the composite salt and Lewis acid salt to obtain a eutectic salt; coating the tablet with the eutectic salt and then calcining, washing, drying, and grinding to obtain V2CT. x MXene material.

[0020] Preferably, the Lewis acid salt includes one or more of copper chloride, cobalt chloride, nickel chloride, or silver chloride.

[0021] Preferably, the composite salt is a mixture of NaCl and KCl in a molar ratio of 1:1.

[0022] Preferably, the mass ratio of V2AlC to the composite salt is 1:5.

[0023] Preferably, the molar ratio of V2AlC to Lewis acid salt is 1:4.

[0024] Preferably, the molar ratio of the composite salt to the Lewis acid salt is 2:0.1.

[0025] Preferably, the roasting temperature is 650~750℃ and the roasting time is 20~40min.

[0026] Preferably, the heating rate during roasting is 5~10℃ / min.

[0027] Preferably, the washing process involves washing with water multiple times, then washing with APS solution for 1 hour, and then washing with water multiple times again.

[0028] Preferably, the drying temperature is 60~80℃ and the drying time is 12~24h.

[0029] Beneficial effects: This invention produces V2CT x MXene materials possess a layered structure and adjustable interlayer spacing. Their surface has functional groups such as -OH and -O, providing more coordination sites and hydrogen bonding sites, enabling them to interact with ammonia molecules and achieve ammonia detection response at room temperature. This invention prepares a V2CT without the inert functional group F using a molten salt method. x MXene material is beneficial for V2CT x The response of MXene materials to ammonia.

[0030] The fourth aspect of the present invention provides the above-described V2CT x V2CT prepared by MXene material preparation method x MXene material.

[0031] The fifth aspect of the present invention provides the above-mentioned alkaline V2CT x Application of MXene material in semiconductor ammonia sensors.

[0032] Preferably, alkalized V2CT x MXene material is dissolved in water to obtain a dispersion. The dispersion is coated onto the surface of the interdigitated electrode using a drop-coating method. After drying at 60~80℃ for 2~3h, a sensitive layer is formed. The sensitive layer is aged at room temperature for 12h to obtain a semiconductor ammonia sensor.

[0033] Beneficial effects: The semiconductor ammonia sensor of the present invention exhibits high sensitivity to ammonia at room temperature, with a response value exceeding 30% at 100 ppm ammonia; it boasts high selectivity and rapid response, with a response time ≤24s, meeting the demand for rapid ammonia detection at room temperature; the semiconductor ammonia sensor of the present invention requires no heating device and operates stably at room temperature, reducing energy consumption and avoiding safety hazards associated with high-temperature operation, thus expanding the application scenarios of ammonia sensors. It is suitable for ammonia detection in flammable, explosive, and low-temperature environments (such as food cold storage warehouses and chemical tank areas); the preparation method of the semiconductor ammonia sensor of the present invention is safe and simple, making it suitable for widespread application. Attached Figure Description

[0034] Figure 1 This is a schematic diagram of the semiconductor ammonia sensor in Application Examples 1-4 of the present invention; Figure 2 V2CT in the embodiments of the present invention x MXene material, alkalized V2CT x XRD patterns of MXene and V2AlC; Figure 3 V2CT in the embodiments of the present invention x MXene materials and alkalized V2CT x XPS spectrum of MXene material; Figure 4 V2CT in the embodiments of the present invention x MXene materials, alkalized V2CT x SEM images of MXene and V2AlC; where (a) and (d) represent V2AlC; and (b) and (e) represent V2CT. x (c) and (f) represent 3M-V2CT x ; Figure 5 The following are the dynamic response curves of the semiconductor ammonia sensor prepared in Examples 1-4 of this invention to different concentrations of ammonia. Figure 6 The graph shows the repeatability test results of the semiconductor ammonia sensor prepared in Examples 1-4 of this invention for ammonia gas. Figure 7 The response recovery time of the semiconductor ammonia sensor for detecting ammonia was obtained in Examples 1-4 of this invention. Figure 8 This is a graph showing the selective response values ​​of the semiconductor ammonia sensor of Application Example 1 of the present invention to various gases. Detailed Implementation

[0035] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0036] Unless otherwise specified, all test materials and reagents used in the following examples are commercially available.

[0037] Unless otherwise specified in the embodiments, all techniques or conditions described in the literature in this field or in accordance with the product manual may be followed. V2AlC was purchased from Foshan Xinxi Technology Co., Ltd.

[0038] Example 1 This embodiment provides an alkalinized V2CT x The preparation method of MXene material specifically includes the following steps: S1. Mix 0.5g of V2AlC, 1.1g of NaCl, and 1.4g of KCl, grind in a mortar for 10 minutes, and compress into tablets using an infrared tablet press. Mix 8.08g of NaCl, 10.3g of KCl, and 1.91g of CuCl2 thoroughly, grind in a mortar for 10 minutes to obtain a eutectic salt. Place the tablets in a crucible, cover with the eutectic salt, and then place the crucible in a muffle furnace, heating to 650℃ at a rate of 5℃ / min and calcining for 30 minutes.

[0039] After calcination, the product was washed with deionized water at least three times to remove eutectic salt impurities; then, it was washed with APS solution (100 ml, 0.5 M) at room temperature for 1 h; and then washed with deionized water at least five times to remove impurities. The product was dried in an oven at 60 °C for 12 h, and then ground to obtain V2CT. x MXene material.

[0040] S2. Dissolve 1.26g of NaOH granules in 10ml of deionized water to prepare a 3M sodium hydroxide solution, then add 0.15g of V2CT. x MXene material was added to sodium hydroxide solution and stirred at room temperature for 12 h. After the reaction, it was washed with deionized water more than 3 times, dried at 60°C for 12 h, and then ground to obtain alkalized V2CT. x MXene material, denoted as 3M-V2CT x .

[0041] Example 2 This embodiment provides an alkalinized V2CT x The preparation method of MXene material in this embodiment differs from that in Example 1 in that the sodium hydroxide solution is 1M, and alkalized V2CT is prepared. x MXene material, denoted as 1M-V2CT x .

[0042] Example 3 This embodiment provides an alkalinized V2CT x The preparation method of MXene material in this embodiment differs from that in Example 1 in that the sodium hydroxide solution is 5M, and alkalized V2CT is prepared. x MXene material, denoted as 5M-V2CT x .

[0043] Example 4 This embodiment provides a V2CT x The preparation method of MXene material in this embodiment differs from that in Example 1 in that step S2 is not performed, thus obtaining V2CT. x MXene material, denoted as V2CT x .

[0044] Application Example 1 This application example provides a method for fabricating a semiconductor ammonia sensor, the sensor being as follows: Figure 1 As shown, it includes an alumina ceramic substrate 1, a gold electrode 2, a conductive adhesive 3, and a platinum wire 4. The gold electrode 2 is disposed on the top of the alumina ceramic substrate 1 to form an interdigitated electrode. The two ends of the gold electrode 2 are connected to the platinum wire 4 through the conductive adhesive 3. A gas-sensitive material coating area 5 is provided on the top of the gold electrode 2.

[0045] The preparation method includes the following steps: 10 mg of alkalized V2CT was prepared from Example 1. x MXene material was dissolved in 1 ml of deionized water and ground thoroughly in a mortar for 30 min to obtain a dispersion with a concentration of 10 mg / mL. 10 μl of the dispersion was pipetted and coated onto the surface of the interdigitated electrode using a drop-coating method, covering the exposed area of ​​the gold electrode 2, specifically in area 5, ensuring uniform coating. The device was then placed in a drying oven at 70°C for 2.5 h to remove moisture from the dispersion and form a preliminary sensitive layer. The device with the sensitive layer was then allowed to age naturally at room temperature for 24 h to further improve the stability of the sensitive layer, resulting in a device based on alkaline V2CT. x A semiconductor ammonia sensor made of MXene material, designated 3M-V2CT x sensor.

[0046] Application Example 2 This application example provides a method for fabricating a semiconductor ammonia sensor. The difference between this application example and Application Example 1 is that the alkalized V2CT prepared in Example 1 is used instead. x The MXene material was replaced with the alkalized V2CT prepared in Example 2. x MXene material, obtained based on alkalized V2CT x A semiconductor ammonia sensor made of MXene material, denoted as 1M-V2CT x sensor.

[0047] Application Example 3 This application example provides a method for fabricating a semiconductor ammonia sensor. The difference between this application example and Application Example 1 is that the alkalized V2CT prepared in Example 1 is used instead. x The MXene material was replaced with the alkalized V2CT prepared in Example 3. x MXene material, obtained based on alkalized V2CT x A semiconductor ammonia sensor made of MXene material, designated 5M-V2CT x sensor.

[0048] Application Example 4 This application example provides a method for fabricating a semiconductor ammonia sensor. The difference between this application example and Application Example 1 is that the alkalized V2CT prepared in Example 1 is used instead. x The MXene material was replaced with the V2CT prepared in Example 4. x MXene material, obtained based on V2CT x A semiconductor ammonia sensor made of MXene material, denoted as V2CT x sensor.

[0049] Experimental Example 1. The MXene materials prepared in Examples 1-4 were characterized, specifically as follows: Figures 2-4 As shown.

[0050] according to Figure 2 As can be seen, the figure shows V2AlC and V2CT. x MXene materials and alkalized V2CT x XRD diffraction pattern of MXene material. V2CT x The MXene material spectrum shows that after etching V2AlC, the characteristic peak at 41.53° disappeared in V2AlC, indicating that the Al layer was successfully etched by the molten salt method, and V2CT was successfully prepared. x MXene. The peak appearing at a low angle (8.32°) corresponds to V2CT. x The (002) crystal plane of MXene material, and also due to V2CT xThe MXene material undergoes partial oxidation during preparation, resulting in characteristic peaks of Al2O3.

[0051] After alkalization with sodium hydroxide, alkalized V2CT x The (002) characteristic peak of MXene material shifted to a lower angle, indicating that the alkali treatment increased V2CT. x The interlayer spacing of MXene material was measured, and it can be seen that compared with the alkalization effect of 1M and 5M sodium hydroxide solutions, the interlayer spacing after alkalization with 3M sodium hydroxide solution is larger. This is beneficial to accelerate the gas diffusion rate and improve the response time of semiconductor ammonia detection.

[0052] according to Figure 3 It can be seen that V, C and O signals are present in the material before and after alkalization, while the peak corresponding to Na 1s appears after alkalization, which also indicates that the material does not contain F end groups.

[0053] according to Figure 4 As can be seen, the figure compares V2AlC and V2CT. x and 3M-V2CT x The morphological characteristics of the original V2AlC were as follows: The original V2AlC exhibited a blocky structure with no open interlayer gaps observed; V2CT was obtained after molten salt etching. x It exhibits a typical two-dimensional layered stacked structure, due to the absence of Al atomic layers, resulting in interlayer gaps between the layers. After further alkalization treatment, the obtained 3M-V2CT... x The nanosheets in the material undergo interlocking and recombination, forming a more loose and open three-dimensional hierarchical structure. (This is similar to V2CT.) x Compared to 3M-V2CT x The significantly larger pore size of the lamellar structure provides more diffusion channels and gas adsorption sites for ammonia adsorption, thereby enhancing the gas-sensing performance.

[0054] 2. The semiconductor ammonia sensors prepared in Application Examples 1-4 were subjected to performance testing. The testing procedure was as follows: The platinum wire electrodes at both ends of the semiconductor ammonia sensors in Application Examples 1-4 were connected to the data acquisition system and the signal acquisition module, respectively, thus completing the assembly. The tests were conducted at room temperature of 25°C and relative humidity of 50% RH.

[0055] A semiconductor ammonia sensor was placed in a gas testing system, and tests were conducted under different concentrations of ammonia, different temperature conditions, and different humidity conditions at room temperature. The resistance changes of the semiconductor ammonia sensor were recorded. The response value of the semiconductor ammonia sensor is defined as follows: , ( Where S represents the sensor's response value for detecting ammonia; This represents the absolute value of the resistance difference of the semiconductor ammonia sensor under two different environments; This indicates the resistance value of the semiconductor ammonia sensor in air. This indicates the resistance value of the semiconductor ammonia sensor in the target gas.

[0056] Ammonia concentrations ranged from 5 to 200 ppm. Repeatability tests were conducted continuously in an ammonia environment at 100 ppm. The response of the semiconductor ammonia sensor to interfering gases such as hydrogen, methane, acetone, nitrogen dioxide, and hydrogen sulfide was also tested to evaluate the selectivity of the semiconductor ammonia sensor. Specific results are as follows: Figures 5-8 As shown.

[0057] according to Figure 5 It can be seen that, under ambient temperature and relative humidity of 50%, when the semiconductor ammonia sensor is exposed to NH3, V2CT x MXene materials and alkalized V2CT x The resistance change trend of the semiconductor ammonia sensor made of MXene material is opposite: as the NH3 concentration increases, V2CT... x The resistance of the semiconductor ammonia sensor made of MXene material gradually increases, while the resistance of the alkalized V2CT increases. x The resistance of the semiconductor ammonia sensor made of MXene material gradually decreases; at the same time, the response value of all semiconductor ammonia sensors increases with the increase of NH3 concentration.

[0058] according to Figure 6 It can be seen that at room temperature and ammonia concentration of 100 ppm, the repeatability results of the four semiconductor ammonia sensors show that the dynamic response of the four semiconductor ammonia sensors to 100 ppm ammonia remained stable in five consecutive cycles, and the response fluctuation was within a reasonable range, indicating that the semiconductor ammonia sensors have good repeatability. Among them, the semiconductor ammonia sensor prepared in Example 1 has the highest response value to 100 ppm ammonia.

[0059] according to Figure 7 It can be seen that at room temperature and an ammonia concentration of 100 ppm, the real-time response curves of the four semiconductor ammonia sensors, V2CT x The response time of the semiconductor ammonia sensor fabricated from MXene material is 68 s, 1M-V2CT. x Sensors, 3M-V2CT x Sensors and 5M-V2CT x The response times of the sensors were 32 s, 24 s, and 28 s, respectively, among which the 3M-V2CT... x The sensor has the shortest response time and the highest response value to ammonia, and a 3M NaOH solution is the optimal alkalization concentration.

[0060] according to Figure 8 It can be seen that at room temperature, 3M-V2CTx The sensor's detection response values ​​for eight gases (methane, toluene, hydrogen, acetone, nitrogen dioxide, hydrogen sulfide, sulfur dioxide, and ammonia) at 100 ppm indicate that the 3M-V2CT... x The sensor's response to ammonia is significantly higher than that to other gases, indicating that it has high selectivity for ammonia.

[0061] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. An alkaline V2CT x The method for preparing MXene material is characterized by, Includes the following steps: S1. V2AlC is ground with a composite salt and then compressed into tablets; the composite salt and Lewis acid salt are ground to obtain a eutectic salt; the eutectic salt is coated on the tablets and then calcined, washed, dried, and ground to obtain V2CT. x MXene materials; Lewis salts include one or more of copper chloride, cobalt chloride, nickel chloride, or silver chloride; S2, V2CT x MXene material was reacted in sodium hydroxide solution, and after the reaction, it was washed, dried and ground to obtain alkalized V2CT. x MXene material.

2. The alkalinized V2CT according to claim 1 x The method for preparing MXene material is characterized by, The mass ratio of V2AlC to the composite salt is 1:5; the composite salt is a mixture of NaCl and KCl in a molar ratio of 1:

1.

3. The alkalinized V2CT according to claim 1 x The method for preparing MXene material is characterized by, The molar ratio of V2AlC to Lewis salt is 1:4; the molar ratio of the complex salt to Lewis salt is 2:0.

1.

4. The alkalinized V2CT according to claim 1 x The method for preparing MXene material is characterized by, The roasting temperature is 650~750℃, the roasting time is 20~40min, and the heating rate during roasting is 5~10℃ / min.

5. The alkalinized V2CT according to claim 1 x The method for preparing MXene material is characterized by, The concentration of the sodium hydroxide solution is 1~5M, and the reaction time is 10~12h.

6. An alkalized V2CT as described in any one of claims 1-5 x Preparation method of MXene material to prepare alkaline V2CT x MXene material.

7. A V2CT x The method for preparing MXene material is characterized by, V2AlC was ground with a composite salt and then compressed into tablets; the composite salt and Lewis acid salt were ground to obtain a eutectic salt; the eutectic salt was then coated onto the tablets and subjected to calcination, washing, drying, and grinding to obtain V2CT. x MXene material.

8. The V2CT according to claim 7 x V2CT prepared by MXene material preparation method x MXene material.

9. An alkaline V2CT as described in claim 6 x Application of MXene material in semiconductor ammonia sensors.

10. The application according to claim 9, characterized in that, Alkalize V2CT x MXene material is dissolved in water to obtain a dispersion. The dispersion is coated onto the surface of the interdigitated electrode using a drop-coating method. After drying at 60~80℃ for 2~3h, a sensitive layer is formed. The sensitive layer is aged at room temperature for 12h to obtain a semiconductor ammonia sensor.